2019
DOI: 10.1111/phn.12634
|View full text |Cite
|
Sign up to set email alerts
|

Trauma informed public health nursing visits to parents and children

Abstract: Adverse Childhood Experiences (ACEs) research has demonstrated a strong correlation between a traumatic childhood and poor health and social status in adulthood. Maternal/child Public Health Nursing (PHN) home visiting teams frequently encounter families experiencing trauma, thus offering a unique opportunity to assist parents in recognizing the potential harm such stress may have for their child. The Sonoma County Field Nursing team developed a trauma‐informed model utilizing ACEs education in a self‐reflecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Preliminary findings of the TIA PHN pilot revealed that clients achieved 80%-100% of health-related outcome measure goals when receiving this approach an average of 12 times over approximately 6 months. 6 The TIA PHN model represents an evidence-informed approach in the process of evaluation with aspirations of eventually becoming an evidence-based model to meet the needs of families with historical and emerging trauma. TIA PHN hopes to impact on the disruption of intergenerational trauma in line with our state's goals.…”
Section: Discussion: Moving the Field Forwardmentioning
confidence: 99%
See 3 more Smart Citations
“…Preliminary findings of the TIA PHN pilot revealed that clients achieved 80%-100% of health-related outcome measure goals when receiving this approach an average of 12 times over approximately 6 months. 6 The TIA PHN model represents an evidence-informed approach in the process of evaluation with aspirations of eventually becoming an evidence-based model to meet the needs of families with historical and emerging trauma. TIA PHN hopes to impact on the disruption of intergenerational trauma in line with our state's goals.…”
Section: Discussion: Moving the Field Forwardmentioning
confidence: 99%
“…36 TIA PHN is an example of an innovative, evidence-informed maternal-child HV approach that acknowledges and addresses the effects of toxic childhood stress to break the cycle of intergenerational trauma. 6 In 2017, rates of homelessness, intimate partner violence, and mental health concerns among families enrolling in the Sonoma County Field Nursing program increased by 17-28% in the months immediately following the 2017 Sonoma Complex Fire, which destroyed more than 5,300 homes and significantly affected the community's overall economy and safety net. 37 Since 2017, the county has experienced nearly annual wildfires, flooding, and the COVID-19 pandemic.…”
Section: Trauma Informed Approach In Public Health Nursing (Tia Phn)mentioning
confidence: 99%
See 2 more Smart Citations
“…977,1318 Nurses and other home visiting professionals provide guidance, coaching, and access to health and social services and have been trained on intercultural competence, trauma-informed care, and disproportionality. 1319,1320 Services were modified as appropriate during the coronavirus disease 2019 (COVID-19) pandemic (see ADAPTATIONS TO THE COVID-19 PANDEMIC).…”
Section: Home Visitingmentioning
confidence: 99%